Rubber tracked bogie-axles with supportive rollers – a new undercarriage concept for log extraction on sensitive soils. Issue 1 (2nd January 2021) - Engler, Benjamin; Hoffmann, Stephan; Zscheile, Matthias
ABSTRACT: Driving forest machines on wet soils causes irreversible soil compaction, often associated with intensive rut formation and inaccessibility of wheeled forest machines for future forest operations. The German forestry equipment manufacturer FHS, Forsttechnik Handel & Service GmbH, engineered a forwarder, the Trac 81/11, equipped with conventional, well-proved bogie-axles embraced by a closed rubber track. At the center of the bogie-axle, four additional supportive rollers are placed to increase the load-carrying section between the tires of the bogie-axle. The study aimed to characterize the principle concept and the trafficability of the forwarder by analyzing the footprint area, the contact pressure, the rut formation on forest sites and the slippage during driving. Therefore, the effective contact area was measured on steel plates and rut formation was analyzed on a case study basis. Results showed that the supportive rollers increase the contact surface area by about 1/3. By this, a decrease of peak loads below the wheels and a more homogenous load distribution were observed. However, the contact surface area is still clearly divided into three parts; the area between the supportive rollers and the wheels does not take any load. Results of the rut formation were diverse: After 20 passes with 26, 700 kg total mass, rut depth varied between 12.6 and 212.5 mm. Overall, the new undercarriage concept of FHS demonstrated a generally positive performance. The engineered forwarder contributes to reduce the environmental impact associated with log extraction.